Geographical and Tick-Dependent Distribution of Flavi-Like Alongshan and Yanggou Tick Viruses in Russia - Kholodilov, Ivan S.; Belova, Oxana A.; Morozkin, Evgeny S.; Litov, Alexander G.; Ivannikova, Anna Y.; Makenov, Marat T.; Shchetinin, Alexey M.; Aibulatov, Sergey V.; Bazarova, Galina K.; Bell-Sakyi, Lesley; Bespyatova, Liubov A.; Bugmyrin, Sergey V.; et al. (Viruses, 2021)
The genus Flavivirus includes related, unclassified segmented flavi-like viruses, two segments of which have homology with flavivirus RNA-dependent RNA polymerase NS5 and RNA helicase-protease NS3. This group includes such viruses as Jingmen tick virus, Alongshan virus, Yanggou tick virus and others. We detected the Yanggou tick virus in Dermacentor nuttalli and Dermacentor marginatus ticks in two neighbouring regions of Russia. The virus prevalence ranged from 0.5% to 8.0%. We detected RNA of the Alongshan virus in 44 individuals or pools of various tick species in eight regions of Russia. The virus prevalence ranged from 0.6% to 7.8%. We demonstrated the successful replication of the Yanggou tick virus and Alongshan virus in IRE/CTVM19 and HAE/CTVM8 tick cell lines without a cytopathic effect. According to the phylogenetic analysis, we divided the Alongshan virus into two groups: an Ixodes persulcatus group and an Ixodes ricinus group. In addition, the I. persulcatus group can be divided into European and Asian subgroups. We found amino acid signatures specific to the I. ricinus and I. persulcatus groups and also distinguished between the European and Asian subgroups of the I. persulcatus group.